Law education for students of Muhammadiyah Pujotomo Junior High School Mertoyudan Magelang to reduce juvenile crime - Yulia Kurniaty; Heniyatun Heniyatun; Suharso Suharso; Puji Sulistyaningsih; Nurwati Nurwati; Bambang Tjatur Iswanto (Universitas Muhammadiyah Magelang, 2023)
Child delinquency often leads to criminal behavior. Students involved in this case in juvenile law are known as Children in Conflict with the Law (ABH). Based on BPHN data for the 2020-2022 period, the number of ABH is 2,338 people. The three types of crimes that are mostly committed by children are theft, narcotics, and abuse. The purpose of this program is to provide legal counseling so that students understand which actions fall into the category of violations of criminal law, the types of legal sanctions, and the length of time the sentence has been served. The methods used are lectures, education and discussion. The results obtained from this program are students are able to understand what actions are included in criminal law violations. In addition, students are encouraged to strengthen their character by being brave in rejecting bad friends' invitations, being careful in choosing friends, not playing late into the night, and not being easily provoked.